Optimization of heavy metal removal from leachate using maize leaves and papaya bark as biosorbent - Fatin Nadzirah Abdul Aziz (2019)
Adsorption process was used to replace the conventional method in removing the heavy metals from leachate. This research was conducted to study the efficiency removal of heavy metals in leachate using treated and untreated of maize leaves and papaya barks. Fourier Transform Infrared Spectrometer (FTIR) was used to observe the functional groups of adsorbent and for the crystallinity of the adsorbent were characterised using X-ray Diffraction (XRD). The batch studies were optimised: pH, agitation rate, adsorbent dosage, and contact period by using Response Surface Methodology (RSM). The optimum conditions predicted by RSM for treated adsorbent were found at pH 6.67, agitation rate (279.71 rpm), contact period (52.25 min) and adsorbent dosage (6.93 g) that indicated about 99.6236% removal efficiency of heavy metals. Contrarily, optimum parameter for untreated adsorbent are pH (5.50), adsorbent dosage (3.08 g), agitation rate (162.40 rpm), and contact period (52.14 min) which represented 92.322% removal efficiency. Adsorption isotherm was employed to study the adsorption capacity and behaviour of the adsorption. Result showed that for treated adsorbent correlation coefficient, R2 is 0.9981 leads to Freundlich model. Untreated adsorbent followed the Langmuir model with R2 of 0.9969.